(untitled) (Advances in Civil and Architectural Engineering, 2023)
Global warming leads to significant long-term changes in climate loads and actions on structures, which must be taken into account when designing buildings. Research in the field of loads on buildings and structures was carried out with the aim to evaluate long-term changes in temperature and humidity of the atmospheric air and to develop a method for forecasting the estimated values of these effects. According to the data of weather stations of Ukraine, it was found that long-term changes of thermal and humidity actions at different weather stations are qualitatively similar, but have significant numerical differences. The increase in air temperature is generally consistent with the known trend of global warming, and relative humidity is characterized by a decrease of the variance at almost constant average annual value. The proposed method of identifying and describing trends in long-term changes in climatic influences can be used in the development of regulatory documents and directly in the design of buildings and structures taking into account the predicted changes in climatic influences during the future life of buildings.